Mustn1 ablation in skeletal muscle results in increased glucose tolerance concomitant with upregulated GLUT expression in male mice - Charles J. Kim; Chanpreet Singh; Christine Lee; Kevin DiMagno; Madison O'Donnell; Marina Kaczmarek; Arhum Ahmed; Jessica Salvo‐Schaich; Alexis Perez; William Letsou; Maria‐Alicia Carrillo Sepulveda; Raddy L. Ramos; et al. (Physiological Reports, 2023)
Abstract Glucose homeostasis is closely regulated to maintain energy requirements of vital organs and skeletal muscle plays a crucial role in this process. Mustn1 is expressed during embryonic and postnatal skeletal muscle development and its function has been implicated in myogenic differentiation and myofusion. Whether Mustn1 plays a role in glucose homeostasis in anyway remains largely unknown. As such, we deleted Mustn1 in skeletal muscle using a conditional knockout (KO) mouse approach. KO mice did not reveal any specific gross phenotypic alterations in skeletal muscle. However, intraperitoneal glucose tolerance testing (IPGTT) revealed that 2‐month‐old male KO mice had significantly lower glycemia than their littermate wild type (WT) controls. These findings coincided with mRNA changes in genes known to be involved in glucose metabolism, tolerance, and insulin sensitivity; 2‐month‐old male KO mice had significantly higher expression of GLUT1 and GLUT10 transporters, MUP‐1 while OSTN expression was lower. These differences in glycemia and gene expression were statistically insignificant after 4 months. Identical experiments in female KO and WT control mice did not indicate any differences at any age. Our results suggest a link between Mustn1 expression and glucose homeostasis during a restricted period of skeletal muscle development/maturation. While this is an observational study, Mustn1's relationship to glucose homeostasis appears to be more complex with a possible connection to other key proteins such as GLUTs, MUP‐1, and OSTN. Additionally, our data indicate temporal and sex differences. Lastly, our findings strengthen the notion that Mustn1 plays a role in the metabolic capacity of skeletal muscle.